Exploring Innovative Methods among Students about the Concept of Sustainability - Laura-Crina Coca; Marius Pislaru (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2023)
The education of young people regarding the concept of sustainability, regardless of the field, has become an essential and topical subject, considering that the evolution of humanity is on an upward slope, not necessarily in the correct or appropriate sense, and our action has an important role. Informing young students about this subsequently contributes to the role that sustainability plays in the company's development strategy. The current paper proposes a study in which several teaching staff from a technical university in Romania and students are questioned about the desire or need to be more informed about sustainability. The study was conducted in two parts. In the first part, students and teaching staff were questioned through online questionnaires. In the second part, they had direct conversations with various company managers, who shared their expectations from employees regarding sustainability. The responses from the questionnaires and the discussions with the managers were kept confidential. Following the study, a platform was created for the students to access guidance and information about sustainability. They also have the opportunity to connect with managers of companies that are already sustainable or aspire to be in the future.
Keywords: I10; 330; sustainability; evolution; education; information; strategy